Evolution of Denmark Strait Overflow Cyclones and Their Relationship to Overflow Surges - M. Almansi; T. W. N. Haine; R. Gelderloos; R. S. Pickart (Geophysical Research Letters, 2020)
Abstract Mesoscale features present at the Denmark Strait sill regularly enhance the volume transport of the Denmark Strait overflow (DSO). They are important for the Atlantic Meridional Overturning Circulation and ultimately, for the global climate system. Using a realistic numerical model, we find new evidence of the causal relationship between overflow surges (i.e., mesoscale features associated with high‐transport events) and DSO cyclones observed downstream. Most of the cyclones form at the Denmark Strait sill during overflow surges and, because of potential vorticity conservation and stretching of the water column, grow as they move equatorward. A fraction of the cyclones form downstream of the sill, when anticyclonic vortices formed during high‐transport events start collapsing. Regardless of their formation mechanism, DSO cyclones weaken starting roughly 150 km downstream of the sill, and potential vorticity is only materially conserved during the growth phase.